2009
DOI: 10.1080/09297040802348028
|View full text |Cite
|
Sign up to set email alerts
|

Interference Control in Children with and without ADHD: A Systematic Review of Flanker and Simon Task Performance

Abstract: The present review systematically summarizes the existing research that has examined two reaction-time-based interference control paradigms, known as the Eriksen Flanker task and the Simon task, in children with and without ADHD. Twelve studies are included, yielding a combined sample size of 272 children with ADHD (M age 9.28 yrs) and 280 typically developing children (M age 9.38 yrs). As predicted, specific disadvantages were found in the ADHD group in terms of reaction time, percentage of errors, and effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
147
3
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(178 citation statements)
references
References 69 publications
15
147
3
8
Order By: Relevance
“…We could not reject the null-hypothesis with regard to emotional interference, meaning that there is not enough support within the current study for a specific emotional interference deficit in children with ADHD. The findings however indicate a generic interference control deficit in the current sample of children with ADHD, which adds to the existing literature on interference control deficits in ADHD (e.g., Lansbergen et al, 2007;Mullane et al, 2009). Future research is warranted investigating the relationship between emotional dysregulation in daily life and generic interference control difficulties in individuals with ADHD.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…We could not reject the null-hypothesis with regard to emotional interference, meaning that there is not enough support within the current study for a specific emotional interference deficit in children with ADHD. The findings however indicate a generic interference control deficit in the current sample of children with ADHD, which adds to the existing literature on interference control deficits in ADHD (e.g., Lansbergen et al, 2007;Mullane et al, 2009). Future research is warranted investigating the relationship between emotional dysregulation in daily life and generic interference control difficulties in individuals with ADHD.…”
Section: Discussionmentioning
confidence: 42%
“…Poor interference control has been argued to be one of the core deficits of ADHD (Barkley, 1997) and many studies have indeed found support for an interference control deficit, although findings across studies are not fully consistent (for meta-analyses, see Lansbergen, Kenemans, & van Engeland, 2007;Mullane, Corkum, Klein, & McLaughlin, 2009;Schwartz & Verhaeghen, 2008;van Mourik, Oosterlaan, & Sergeant, 2005). The mixed findings may be explained by several factors, such as the task used, the calculation of the interference effect, and the heterogeneity of ADHD.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Heil et al, 2000;Johnstone et al, 2009;Mullane et al, 1 These group differences are likely due to the inability of children with AD/HD to apply their knowledge and abilities to the psychometric instruments, as opposed to any inherent differences. Therefore, reading age and IQ were not included as covariates in order to preserve the clinical relevance of these data.…”
Section: Task Performancementioning
confidence: 99%
“…For instance, inhibition has been measured using a number of different tasks, including the Stroop task (MacLeod, Dodd, Sheard, Wilson, & Bibi, 2003;Stroop, 1935), the Simon task (Hommel, 2011), the Eriksen flanker task (Eriksen & Eriksen, 1974;Mullane, Corkum, Klein, & McLaughlin, 2009), the antisaccade task (Luna, 2009;Munoz & Everling, 2004), and the go/no-go task (Cragg & Nation, 2008). Updating has been measured by the Corsi blocks task (Lezak, 1983); n-back tasks (Owen, McMillan, Laird, & Bullmore, 2005); counting, reading, and operation span tasks (Barrouillet, Gavens, Vergauwe, Gaillard, & Camos, 2009;Case, 1995;Daneman & Carpenter, 1980;Turner & Engle, 1989); and symmetry span tasks (Kane et al, 2004).…”
Section: The Structure and The Measures Of Efsmentioning
confidence: 99%